Cardiac Surgery and Transcatheter Intervention for Valvular Heart Disease in Carcinoid Syndrome: Risk Factors, Outcomes, and Evolving Therapeutic Strategies - Mariagrazia Piscione; Valeria Cammalleri; Giorgio Antonelli; Valeria Maria De Luca; Myriam Carpenito; Dario Gaudio; Nino Cocco; Antonio Nenna; Carmelo Dominici; Antonio Bianchi; Francesco Grigioni; Gian Paolo Ussia (Journal of Cardiovascular Development and Disease)
Carcinoid heart disease (CHD) affects right-sided valves and causes significant mortality and morbidity. Even though the pathophysiology of the disease is not entirely understood, it is known that chronic exposure to high levels of circulating serotonin is the main factor responsible for developing valvular heart disease. Cardiac imaging plays a critical role in the management of CHD, so the final diagnosis can be performed through multimodal imaging techniques and the measurement of biomarkers. Moreover, in observational studies, surgical treatment of carcinoid-induced valve disease has been found to improve outcomes. Despite advancements in pre-operative preparation in recent years, mortality rates remain high in elderly patients and those with multiple comorbidities due to the risk of intra-operative carcinoid crisis and high post-operative bleeding. In this comprehensive review, we will analyze the causes of carcinoid syndrome and how it can result in severe right heart failure. The role of different imaging modalities in detecting heart valve disease will be discussed together with the therapeutic options at our disposal, such as medical treatment, surgery, and the novel role of transcatheter intervention.